2012
DOI: 10.1051/0004-6361/201219205
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of LS 5039 and PSR J1825−1446

Abstract: Context. The gamma-ray binary LS 5039 and the isolated pulsar PSR J1825−1446 were proposed to have been formed in the supernova remnant (SNR) G016.8−01.1. Aims. We aim to obtain the Galactic trajectory of LS 5039 and PSR J1825−1446 to find their origin in the Galaxy, and in particular to check their association with SNR G016.8−01.1 to restrict their age. Methods. By means of radio and optical observations we obtained the proper motion and the space velocity of the sources. Results. The proper motion of PSR J18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 130 publications
(196 reference statements)
3
24
0
Order By: Relevance
“…Therefore it is unclear if the derived peculiar motion originates from a kick during the stellar core collapse or if it was intrinsic to the system beforehand. We note that the derived motion is similar to the motion of 26 ± 8 km s −1 observed in the gamma-ray binary PSR B1259−63 (Miller-Jones et al 2018), but lower than the motion of ∼ 140 km s −1 observed in LS 5039 (Moldón et al 2012b), and higher than the motion of ∼ 16 km s −1 observed in LS I +61 303 (Wu et al 2018). In any case, these motions are well below the velocities observed in isolated pulsars (see e.g., Chatterjee et al 2005), as expected for binary systems.…”
Section: Peculiar Motionsupporting
confidence: 68%
“…Therefore it is unclear if the derived peculiar motion originates from a kick during the stellar core collapse or if it was intrinsic to the system beforehand. We note that the derived motion is similar to the motion of 26 ± 8 km s −1 observed in the gamma-ray binary PSR B1259−63 (Miller-Jones et al 2018), but lower than the motion of ∼ 140 km s −1 observed in LS 5039 (Moldón et al 2012b), and higher than the motion of ∼ 16 km s −1 observed in LS I +61 303 (Wu et al 2018). In any case, these motions are well below the velocities observed in isolated pulsars (see e.g., Chatterjee et al 2005), as expected for binary systems.…”
Section: Peculiar Motionsupporting
confidence: 68%
“…This effect is particularly severe when the number of degrees of freedom is relatively small, as is typically the case for astrometric observations. Accordingly, a useful cross-check is a bootstrap test, which has been widely used in past pulsar astrometry projects (Chatterjee et al 2009;Deller et al 2012;Moldón et al 2012), since it can be used to estimate errors on fitted parameters when the underlying measurement errors are poorly known (Efron & Tibshirani 1991). Bootstrapping involves creating a large number of test data sets, where each data set is constructed by sampling with replacement from the pool of measured astrometric positions.…”
Section: Astrometric Fits and Resultsmentioning
confidence: 99%
“…Proper motion of PSR B1822−14 in RA and Dec (top two panels) and the residuals of the VLBI data compared to the best linear fit (bottom two panels). The first two epochs are from archival VLA data (Frail & Scharringhausen 1997), the next four are VLA and VLBA observations (Moldón et al 2012), and the final point is from our recent VLBA observation. Our position is consistent with the proper motion measured by Moldón et al (2012).…”
Section: Large Dm Contributions From Single Hii Regions and Effect Onmentioning
confidence: 99%